Ideals of counterculture in the works of Charles Bukowski - Drake, Daniel (Univerzita Pardubice, 2018)
This thesis deals with the counterculture period in the United States of America. It defines the term and divides it into respective movements. It describes the different approaches to literature taken by the different movements and, on the basis of the information uncovered, categorises Charles Bukowski. The paper then analyses Bukowski's stories and poems in order to discover the counterculture features that he implemented into his work.
Ideály kontrakultury v díle Charlese Bukowského
Keywords: counterculture; Bukowski, Charles; Beats; kontrakultura; Bukowski, Charles; beatníci